Pelaksanaan Jaminan Hak Tanggungan Kapal Laut Antara PT. Bank Nasional Indonesia Cabang Jambi Dengan PT. Sabak Indah Di Tanjung Jabung Timur - Nurfauzia Nurfauzia (Jurnal LEX SPECIALIS, 2011)
Although the bank is obliged to channel funds to those who need and would benefit greatly from the loans they provide, but not the PT. Bank Nasional Indonesia directly provide loans to those in need, but rather ask for a reassurance to those who need it in order to secure the funds loaned to return, although that is not returned directly by those who need, but can be obtained from the sale of collateral submitted tersebut.Dikaitkan with the credit agreement concluded between the PT. Sabak Indah with PT. Bank Nasional Indonesia, loan guarantees which are held mortgages of ships. Due to the ship remained under the control of PT. Sabak Indah, it is possible in the operational implementation of ships is facing an unwanted risks, such as ships were damaged. If there is risk of damage to the ship which is very undesirable affect the existing mortgage at the bank who hold, as it can only mortgages can no longer be used as intended. Key Note : Rights of Warranty Liability